(untitled) (Journal of Geography and Environmental Management, 2026)
Groundwater in Kazakhstan is becoming an increasingly vital resource for ensuring long-term water and food security in the face of climate change, growing population demands, seasonal variability, and limited surface water availability. This study evaluates groundwater quality and soil infiltration capacity in Eastern Kazakhstan to assess the potential for implementing Managed Aquifer Recharge (MAR) as a sustainable water management approach. Hydrochemical analysis revealed predominantly calcium–magnesium bicarbonate waters with low mineralization, suitable for both irrigation and domestic use, indicating generally good groundwater quality. Field tests conducted using the Boldyrev infiltration method demonstrated moderate to high soil permeability in alluvial and sandy-gravel deposits, confirming favorable recharge conditions. Among the areas studied, the Zharbulak, Katynsuy, and Kuraylin deposits were identified as the most promising sites for MAR pilot projects. Overall, the results highlight MAR as a practical, cost-effective, and climate-resilient tool for strengthening regional water security and supporting sustainable agricultural development in Kazakhstan.